Unpacking the peace pillar of the Triple Nexus. Issue 3 (3rd April 2023) - Sanchez Garcia, Eric
ABSTRACT: The stronger integration and coordination among Humanitarian, Development and Peacebuilding actors (hereafter, the Triple Nexus), is gaining traction in the international development debate. However, there is a sense of deep unease among some civil society organisations that adding peace into humanitarian work may compromise their impartiality. This paper will address some of civil society's reservations on the Triple Nexus by reframing peace around human security, steering away from traditional conceptions of militarised security. It will also provide examples of how peace can be realised as part of an integrated Triple Nexus approach. Finally, adaptive peacebuilding will be explored to exemplify how being agile is key to delivering on the Triple Nexus.